Erratum to “Integrative analysis of cuproptosis-related lncRNAs: Unveiling prognostic significance, immune microenvironment, and copper-induced mechanisms in prostate cancer” [Cancer Pathog Ther, 3 (2025):48–59] - Zhong, Haitao; Lai, Yiming; Ouyang, Wenhao; Yu, Yunfang; Wu, Yongxin; He, Xinxin; Zeng, Lexiang; Qiu, Xueen; Chen, Peixian; Li, Lingfeng; Zhou, Jie; Luo, Tianlong; et al. (Cancer pathogenesis and therapy, 2025)
[This corrects the article DOI: 10.1016/j.cpt.2024.03.004.].